Precipitated calcium carbonate from industrial waste for paper making - Rohaya Othman,; Nasharuddin Isa,; Anuar Othman, (Universiti Kebangsaan Malaysia, 2015)
In this study carbide lime waste was used as raw material to produce precipitated calcium carbonate (PCC). Carbide lime is an industrial waste from acetylene gas industry which uses limestone in its production. The use of PCC as fillers in paper making can reduce the production cost and improve the paper properties such as opacity and brightness. PCC can be produced from carbide lime waste by ionic sucrose solution method. The sucrose solution of Brix 10° was first prepared by dissolving sugar (sucrose) in water followed by dissolution of carbide lime waste in the sucrose solution. The sucrose solution which had turned milky was then filtered to obtain a clear solution known as pregnant solution. The pregnant solution that contained calcium ions was subsequently used to produce PCC by introducing CO2 gas into the pregnant solution. The process is known as carbonation. The PCC was then used as fillers in paper making. The production of PCC by using calcium hydroxide as starting material was also carried out for comparison purposes. Based on the results, PCC prepared from carbide lime had purity of 98.14% while the one prepared from calcium hydroxide had 98.66%. Meanwhile, analysis of the paper properties demonstrated that both products gave equally good results. This proves that PCC prepared from industrial waste can be used for paper making.